2004
DOI: 10.1111/j.1365-2222.2004.01897.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification by immunoblot of venom glycoproteins displaying immunoglobulin E‐binding N‐glycans as cross‐reactive allergens in honeybee and yellow jacket venom

Abstract: The data confirm the proposed role of carbohydrate-specific IgE in double positivity to HB and YJ venom and shed new light on some previously described minor hymenoptera allergens of uncertain clinical significance. The consideration of carbohydrate-specific IgE may allow to discriminate between patients with potentially relevant and patients with non-relevant double sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
2
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 39 publications
2
92
2
8
Order By: Relevance
“…Previous studies have shown that venom-allergic individuals can develop IgE antibodies against specific carbohydrate structures. The N-glycan structures containing -1,3-linked fucose residues at the glycan core have been suggested to be involved in this type of IgE-mediated cross-reactivity and thus are considered to be a major cause of in vitro double positivity in honeybee and vespid-allergic individuals (Hemmer et al, 2001(Hemmer et al, , 2004. Interestingly, in the present study only one site at Asn99 was found to carry this type of N-glycan.…”
Section: N-glycosylation Of Natural Ves Vmentioning
confidence: 40%
See 1 more Smart Citation
“…Previous studies have shown that venom-allergic individuals can develop IgE antibodies against specific carbohydrate structures. The N-glycan structures containing -1,3-linked fucose residues at the glycan core have been suggested to be involved in this type of IgE-mediated cross-reactivity and thus are considered to be a major cause of in vitro double positivity in honeybee and vespid-allergic individuals (Hemmer et al, 2001(Hemmer et al, , 2004. Interestingly, in the present study only one site at Asn99 was found to carry this type of N-glycan.…”
Section: N-glycosylation Of Natural Ves Vmentioning
confidence: 40%
“…However, as far as we know, the sugar moieties of rApi m 2 have not yet been modelled and/or characterized. In contrast, it has been shown that natural Api m 2 is glycosylated at Asn263 with a Man 6(Man 3)Man 4GlcNAc 4(Fuc 3)GlcNAc -Asn type oligosaccharide containing six or seven sugar rings (Hemmer et al, 2004;Kolarich & Altmann, 2000). A corresponding glycosylation site is not found in Ves v 2.…”
Section: N-glycosylation Of Natural Ves Vmentioning
confidence: 94%
“…Venoms of the yellow jacket species considered so far contain three major allergens: antigen 5 (Ag5 or Ves x 5), phospholipase (PLA or Ves x 1) and hyaluronidase (Hyase or Ves x 2), the latter being a glycoprotein [2][3][4][5][6]. Other proteins such as Vmac1 and Vmac3 have additionally been described as minor allergens from V. maculifrons [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of our results it is noteworthy that core N-glycans modified with (α1-3)-Fuc and/or (β1-2)-Xyl residues in honeybee (HB) and vespid venoms [23] are proposed as immunogens responsible for cross-sensitisation to HB and yellow jacket (YJ). Whether protection of gpMuc against Echis carinatus venom depends upon the presence of the same (α1-3)-Fuc and/or (β1-2)-Xyl residues is now under study in our laboratories.…”
Section: Discussionmentioning
confidence: 79%